Multi-scale crack closure measurements with digital image correlation on Haynes 230 - Stefano Beretta; Silvio Rabbolini; Angelo Di Bello (Fracture and Structural Integrity)
An experimental campaign was developed to study fatigue crack growth in Haynes 230, a Ni-based superalloy. The effects of crack closure were investigated with digital image correlation, by applying two different approaches. Initially, full field regression algorithms were applied to extract the effective stress intensity factor ranges from the singular displacement field measured at crack tips. Local closure measurements were then performed by considering crack flanks relative displacements. Two points virtual extensometers were applied in this phase. Experimental results were then compared to the reference da/dN –ΔKeff curve: it was found that the correct estimation of crack opening levels shifts all the experimental points on the reference curve, showing that DIC can be successfully applied to measure crack closure effects.